Hardware hacking projects for geeks - Fullam, Scott F. (Scott Francis) (O'Reilly, 2004)
Put a hacker in a room with a Furby for a weekend and you'll hear a conversation that's fairly one-sided in its originality. Toss in an 802.11b network card, a soldering iron, wire cutters, a logic probe, and a few other carefully selected tools and materials and you'll have potential. Add a copy of Hardware Hacking Projects for Geeks and by the end of the weekend that Furby will be saying things you never imagined. From building an Internet toaster to creating a cubicle intrusion detection system, Hardware Hacking Projects for Geeks offers an array of inventive, c.